The effect of Psidium guajava Linn leaf extract on Candida albicans adherence and the transversal strength of acrylic resin - Amiyatun Naini; Sherman Salim (Dental Journal (Majalah Kedokteran Gigi), 2008)
Denture stomatitis is an inflammation of oral cavity due to removable denture wearing. Prevention of denture stomatitis can be effectively done by using mouth rinsing. Currently, Indonesian government is actively promoting traditional herbal medicine as an alternative medicine such as Psidium guajava Linn leaf which has an anti bacterial and anti fungal ability. The purpose of this study was to know the effective concentration and soaking duration to reduce Candida albicans without lowering transversal strength of acrylic resin. This experimental laboratory study was using heat cured acrylic resin plate without surface polishing. The concentration of Psidium guajava Linn leaf extract used in this study were 32%, 34%, 36%, and 38% respectively with 15 minutes, 30 minutes, 1 hour and 8 hours soaking duration. The transversal strength was measured in the same concentration with 2 days, 10 days and 60 days soaking duration. Sterile aquadest was used as control. Two direction ANOVA and LSD test were used in data analysis. The result showed significant difference in the number of Candida albicans colony among concentrations and soaking durations. Significant difference was also found in transversal strength among concentrations and soaking durations. It is concluded that the extract of Psidium guajava Linn leaf in 38% concentration with 8 hours soaking duration will lower the Candida albicans colony, whereas 38% concentration with 60 days soaking duration will lower the transversal strength but it is still above the standard value.